Improving the Productivity of National Offices for Statistics - Medina Giopp, Alejandro (World Bank, Washington, DC, 2020)
For decades, policy experts’ and practitioner consensus has been growing about the crucial role quality data plays in informing policy making. This has led to investment and projects to increase quality data availability. But progress has been slow, as reflected by slow improvement in country statistical capacity, many countries remain data deprived. The IPNOS toolkit is based on the notion that producing more and better statistics, while requiring adequate resources, should also be efficient. Various initiatives assess national statistical systems’ (NSS) and data production. The World Bank’s IPNOS initiative complements existing kits, providing in-depth analytical tools to evaluate the efficiency of national statistical offices (NSOs), including costs, data quality, and NSO management. IPNOS application in 3 countries has identified bottlenecks and areas for improvement to inform data policies.